Answer:
binomial
Step-by-step explanation:
Answer:
y = x² - 13x + 36
Step-by-step explanation:
Given the zeros x = 4 and x = 9, then the corresponding factors are
(x - 4) and (x - 9)
The polynomial is then the product of the factors
y = (x - 4)(x - 9) ← expand using FOIL
y = x² - 13x + 36
show me a example please
Step-by-step explanation:
\
Answer:
The answer would be - 11.
Step-by-step explanation:
9 + 8 = 17
17 - 6 = 11.
4 - 5 = 4 + - 5 = - 1
11(- 1) = 11 × - 1 = - 11
Therefor, your answer would be - 11.
Hope this helps!